(untitled) (Research, Society and Development, 2020)
Objective: to describe the successful treatment of a 5mm-sized granular cell ameloblastoma in the posterior region of the maxilla, discovered in a routine examination during the evaluation of an oroantral communication. Patients and methods: the case repot is presented based on a simple literature review of the last 10 years with the descriptors (Ameloblastoma; Maxilla; Surgery; Oral Diagnosis; Neoplasms) in Pubmed. Treatment consisting of fistulectomy and closure of the oroantral communication with the buccal fat pad and vestibular flap was associated with enucleation and curettage of the adjacent lesion under local anesthesia. Results: a satisfactory evolution was observed in the 1 year postoperative, with a good healing aspect and no signs of oroantral complications or recurrence of the lesion. Conclusion: for minor lesions, more conservative treatment proposals such as enucleation represent a viable alternative and, in addition, the use of adjuvant techniques such as curettage can offer benefits when the differential diagnosis includes more aggressive lesions or with a higher rate of recurrence.